2022
DOI: 10.3389/fgwh.2022.795532
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Accessing Addiction Treatment for Women at Risk of Homelessness

Abstract: Women remain under-represented in addiction treatment, comprising less than a third of clients in treatment services. Shame, stigma, and fear of legal and social repercussions (e.g., child protection involvement) are major barriers impacting on treatment-seeking for women. This is compounded for women at risk of homelessness, with practical and logistical reasons for not engaging in treatment. We conducted a qualitative study with both clinicians and service-providers, and women with lived experience of addict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…As such, emerging evidence suggests that integrating services for pregnancy and/or child-care into treatment services for women with SUD, may lead to improved parenting outcomes, such as reduced risk of maltreatment and increased parenting satisfaction [ 25 ]. In general, research has underscored the need for more gender-responsive, female-specific, SUD treatment options, and the elimination of gender-specific barriers to treatment access, such as familial responsibilities, intimate partner violence, and the heightened stigma and shame associated with accessing treatment [ 24 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…As such, emerging evidence suggests that integrating services for pregnancy and/or child-care into treatment services for women with SUD, may lead to improved parenting outcomes, such as reduced risk of maltreatment and increased parenting satisfaction [ 25 ]. In general, research has underscored the need for more gender-responsive, female-specific, SUD treatment options, and the elimination of gender-specific barriers to treatment access, such as familial responsibilities, intimate partner violence, and the heightened stigma and shame associated with accessing treatment [ 24 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the need for research based in real-world settings, and drawing from practice-based evidence, such as that derived from this service audit to delineate intersections between social and clinical diagnostic complexity factors. For example, in a previous study examining a range of barriers to service access for women with homelessness and AOD problems, we found that it was the intersection between a range of key social factors alongside the system and individual level (emotional and psychological) factors that underpinned challenges in access to care (Rizzo et al , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…8 Other barriers to seeking and receiving help include reports of a feeling of shame or stigma as well as a fear of government agencies. 9 Cultural appropriateness of services delivered and innate racial bias have also been reported as barriers. 10 As a result, significant proportions are without treatment or flexible treatment options.…”
Section: Introductionmentioning
confidence: 99%